THE DEEPER LIFE CAMPUS FELLOWSHIP/CHURCH AND THE CULTURE OF PICTURES AS REPRESENTATION OF IDEAS AND AESTHETICS IN AN ENVIRONMENT OF MORAL AND SOCIO-POLITICAL LETHARGY - Owoeye, S.A.; Aluko, O.P. (European Scientific Journal, ESJ, 2014)
In this era of various electro-media devices, many Pentecostal churches still prefer to illustrate their beliefs with powerful pictures in their churches. This culture of illustrating the unknown with known still; persists among many Pentecostal/African Independent churches in South-Western Nigeria. Perhaps this culture is retained because of the prevalent moral decadence in Nigerian society or probably because of the popular belief that visual aids impress ideas more in people’s minds than mere audio messages. Some pictures are designed to emphasize sexuality and gender relations. Some of them are to encourage submissiveness and decency in the sexuality of women. They equally emphasize the importance of trust and moral integrity, especially in the selection of sexual partners, more so, when the spread of HIV/AIDS has been linked to the growing promiscuity in both men and women in and outside the church. Emphasis on the kingdom of God and the last judgment is also responsible for a number of pictures which are meant to show heaven and hell more graphically. In the light of this continuous usage of picture as both symbols of beliefs and aesthetics, this paper examines the use of pictures by the DCLF in OAU to depict spiritual messages.